Changes in Nutritional State and Cardiovascular Parameters in Alimentary Obese Children after a Month-Long Stay in Children's Treatment Center - Ksenia Budinskaya; Ondřej Pírek; Natálie Rafčíková; Olga Nádeníčková; Kateřina Bednaříková; Hana Hrstková; Petr Dobšák; Zuzana Nováková (MDPI AG, 2022)
Childhood and adolescent obesity has become an important public health issue, as it leads to higher risk of cardio-metabolic, orthopedic, and psychological comorbidities. The aim of this study was to evaluate the changes in nutritional state and cardiovascular system parameters in obese children. Sixty respondents aged 9-17 years with alimentary obesity participated in this research. Anthropometric parameters (body weight (BWT), body mass index (BMI), percentage of body fat (%), waist and hip circumference (WC and HC), waist-hip ratio (WHR)) and cardiovascular parameters (systolic and diastolic blood pressure (SP and DP), cardio-ankle vascular index (CAVI), ankle-brachial index (ABI), pulse wave velocity and its variability (PWV and PWVV), and parameters of pulse wave analysis) were measured. Every respondent went through two sets of measurements, the first (I.) after their admission to the children's hospital and the second (II.) at the end of their one-month-long therapeutic stay. Statistically significant differences between measurements I. and II. were observed in the following parameters: BWT (p < 0.01), BMI (p < 0.01), WC (p < 0.01), HC (p < 0.01), DP (p < 0.01), PWV (p < 0.05), and ABI (p < 0.01). The results of this study show that obesity has a mostly negative impact on the cardiovascular health of affected children, with likely negative results in their adulthood.